Patient selection and the volume effect in pancreatic surgery: unequal benefits?. Issue 10 (6th June 2014) - Bliss, Lindsay A.; Yang, Catherine J.; Chau, Zeling; Ng, Sing Chau; McFadden, David W.; Kent, Tara S.; Moser, A. James; Callery, Mark P.; Tseng, Jennifer F.
Abstract Background The volume effect in pancreatic surgery is well established. Regionalization to high‐volume centres has been proposed. The effect of this proposal on practice patterns is unknown. Methods Retrospective review of pancreatectomy patients in the Nationwide Inpatient Sample 2004–2011. Inpatient mortality and complication rates were calculated. Patients were stratified by annual centre pancreatic resection volume (low <5, medium 5–18, high >18). Multivariable regression model evaluated predictors of resection at a high‐volume centre. Results In total, 129 609 patients underwent a pancreatectomy. The crude inpatient mortality rate was 4.3%. 36.0% experienced complications. 66.5% underwent a resection at high‐volume centres. In 2004, low‐, medium‐ and high‐volume centres resected 16.3%, 24.5% and 59.2% of patients, compared with 7.6%, 19.3% and 73.1% in 2011. High‐volume centres had lower mortality (P < 0.001), fewer complications (P < 0.001) and a shorter median length of stay (P < 0.001). Patients at non‐high‐volume centres had more comorbidities (P = 0.001), lower rates of private insurance (P < 0.001) and more non‐elective admissions (P < 0.001). Discussion In spite of a shift to high‐volume hospitals, a substantial cohort still receives a resection outside of these centres. Patients receiving non‐high‐volume care demonstrate less favourable comorbidities, insurance and urgency of operation. The implications are twofold: already disadvantaged patients may not benefit from the high‐volume effect; and patients predisposed to do well may contribute to observed superior outcomes at high‐volume centres.